Measurable residual disease in chronic lymphocytic leukemia - Benintende, Giulia; Pozzo, Federico; Innocenti, Idanna; Autore, Francesco; Fresa, Alberto; D’Arena, Giovanni; Gattei, Valter; Laurenti, Luca (Frontiers in Oncology, 2023)
Measurable residual disease (MRD) is defined as the presence of residual cancer cells after treatment in patients with clinically undetectable disease, who would otherwise be considered in complete remission. It is a highly sensitive parameter which indicates the disease burden and predicts survival in this setting of patients. In recent years, MRD has gained a role in many hematological malignancies as a surrogate endpoint for clinical trials: undetectable MRD has been correlated to longer progression free survival (PFS) and overall survival (OS). New drugs and combinations have been developed with the aim to achieve MRD negativity, which would indicate favorable prognosis. Different methods to measure MRD have also been devised, which include flow cytometry, polymerase chain reaction (PCR) and next generation sequencing (NGS), with different sensitivity and accuracy in evaluating deep remission after treatment. In this review, we will analyze the current recommendations for the detection of MRD, with particular focus on its role in Chronic Lymphocytic Leukemia (CLL), as well as the different detection methods. Moreover, we will discuss the results of clinical trials and the role of MRD in new therapeutic schemes with inhibitors and monoclonal antibodies. MRD is not currently used in the clinical practice to evaluate response to treatment, due to technical and economical limitations, but it’s gaining more and more interest in trials settings, especially since the introduction of venetoclax. The use of MRD in trials will likely be followed by a broader practical application in the future. The aim of this work is to provide a reader-friendly summary of the state of art in the field, as MRD will soon become an accessible tool to evaluate our patients, predict their survival and guide physician’s therapeutic choices and preferences.